2019
DOI: 10.1111/jace.16666
|View full text |Cite
|
Sign up to set email alerts
|

Uniform colloidal spheres for RE3BO6 (RE = Eu‐Yb, Y) and excitation‐dependent luminescence of Y3BO6:Eu3+ red phosphor

Abstract: Phosphor particles of spherical shape and uniform size are desired for high‐definition displays to improve the resolution and the overall luminescent performance. However, the synthesis of RE3BO6 spherical particles is a considerable challenge in materials science. Here, uniform spheres of RE3BO6 (RE = Eu–Yb, Y) have been converted from their colloidal precursor spheres synthesized via homogeneous precipitation. The amorphous precursor spheres are solid particles with decreased boron going from the surfaces to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Transmittance of the prepared GAP:Eu 3+ ceramic film was analyzed in Figure 5c. A broad and strong band is found in the transmittance curve at the range of 250-400 nm, which is arising from the charge-transfer absorption of O 2− -Eu 3+ [32]. The shoulder near the intense band is assigned to the 8 S 7/2 -6 I J transition of Gd 3+ [33].…”
Section: Optical Properties Of Gap:eu 3+ Transparent Ceramic Filmmentioning
confidence: 92%
See 2 more Smart Citations
“…Transmittance of the prepared GAP:Eu 3+ ceramic film was analyzed in Figure 5c. A broad and strong band is found in the transmittance curve at the range of 250-400 nm, which is arising from the charge-transfer absorption of O 2− -Eu 3+ [32]. The shoulder near the intense band is assigned to the 8 S 7/2 -6 I J transition of Gd 3+ [33].…”
Section: Optical Properties Of Gap:eu 3+ Transparent Ceramic Filmmentioning
confidence: 92%
“…Monitoring the wavelength at 618 nm, a broad and strong band is observed in PLE spectra at the range of 200-300 nm, whose maximum is located at 254 nm. The electron transition of O 2− -Eu 3+ mainly contributes to the intense band (Figure 6a), which is usually called the charge-transfer band (CTB) [32]. However, the very weak peaks at the wavelength range of 300-500 nm are assigned to the intra-4f electronic transitions of the Eu 3+ ion, but they are almost invisible because of the rather strong CTB.…”
Section: Optical Properties Of Gap:eu 3+ Transparent Ceramic Filmmentioning
confidence: 99%
See 1 more Smart Citation
“…8 It was previously reported that GdBO 3 , 17–19 Gd(BO 2 ) 3 , 20 and Y 3 BO 6 (ref. 21 and 22) are excellent host lattices to dope a high amount of Eu 3+ ions; however, only a low quantum efficiency of 14.30% could be obtained under the excitation of NUV light. It is well known that the introduction of dopants at a critical concentration in a material often leads to a decrease in photoluminescence (PL) intensity, resulting in a lower quantum efficiency of the synthesized material.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to uncompatibilized blend due to the elastomeric nature of SEBS in SEBS-g-MAH. Zhu et al [6] carried out a research on PP/PET (80/20 wt.) blend with polypropylene grafted maleic anhydride and diallyl phthalate(PP-g-MAH/DAP) as a compatibilizer and observed better size distribution, dispersion, better mechanical properties with respect to the uncompatibilized PP/recycled PET blend.…”
Section: Introductionmentioning
confidence: 99%